Human Resource Practices and Turnover Intention: The Moderating Role of Organizational Commitment - I Ketut R. Sudiarditha, Widya Parimita, Agus Wibowo, Zahrania Maudy Pramasitha, Bagus Shandy Narmaditya (International Journal of Advanced Science and Technology, 2020)
The study aims at examining the impact of human resource practices toward turnover intention and investigating the moderating role of organizational commitment. The study was conducted on 134 respondents with data analysis techniques using path analysis. The results of the study are empirically proven that human resource practices significantly influence organizational commitment, while organizational commitment significantly influences the intention to leave the organization. In addition, human resource practices do not directly influence the intention to leave the organization, and human resource practices have a relationship with the intention to leave the organization mediated by organizational commitment. This study found that organizational commitment mediated the proposed relationship between human resource practices and turnover intentions for millennial employee sales representatives. Limitations and suggestions for future research are continued, which puts more emphasis on distributors in other sectors. Keywords: human resource practices, organizational commitment, turnover intention